Research on the Working Group and Its Adjustment Mechanism for Serving Large Construction Projects - Li, Zhongmei (Journal of Theory and Practice in Economics and Management, 2025)
As a special working group with Chinese characteristics, it has the advantages of both matrix structure and temporary organization. It has the unique advantages of flat organizational structure, flexible and professional personnel, and efficient and orderly operation in the governance of non-routine affairs, which effectively makes up for the shortcomings of the traditional bureaucratic system. Different from the research on special working groups that focuses on the macro level, the special working groups operating at the grassroots level follow the logic of problem-solving and are buffers connecting the superior government and the grassroots society. Based on the establishment goals and survival cycle of the special working groups, this article divides the special working groups into four categories: emergency task attack type, routine task execution type, simple problem solving type, and complex problem adaptation type. The article takes the special working group serving the construction of Huawei’s R&D center as a case study and delineates it as a complex problem adaptation type special working group. The adaptation mechanism of the special working group in the process of serving the construction of large-scale projects is studied. The study found that this type of special working group achieved cross-bureaucratic adaptation through resource calling mechanism, line communication mechanism, and joint consultation and linkage mechanism, effectively resolved many contradictions and conflicts in the process of project promotion, and laid the foundation for the orderly promotion of the project.